ANALISIS SWOT DAN BISNIS MODEL CANVAS DALAM PEMBUKAAN UMKM PADA MASA PANDEMI COVID 19 - Rastryana, Ulta (2021)
The Covid 19 pandemic that is currently occurring in Indonesia has caused Indonesia to experience symptoms of a recession, where it is difficult to find jobs. This study aims to determine the development of UMKM during a pandemic and how many residents have turned into entrepreneurs. This study uses the SWOT research method and the creation of a canvas model business concept. Respondents of this study were 30 UMKM in the kelurahan Rawa Badak Selatan in North Jakarta and the data were collected through the interview method from several informants and observations of 30 UMKM. This study shows the results, namely the effect of SWOT analysis and making the business concept of the canvas model on UMKM, which can increase income during the Covid Pandemic 19.